Obsolescence of the obsolescing bargain: Why governments must get investor-state contracts right - Karl P. Sauvant; Louis T. Wells (Columbia University, Columbia Center on Sustainable Investment (CCSI), 2021)
Gone are the days when governments could easily renegotiate natural resource contracts if investors reaped bonanzas from rising resource prices, surprisingly rich discoveries, or terms that were too favorable. Today, international investment agreements protect investors from renegotiation. Now, governments must get initial contracts right, including providing for possible future events.
Keywords: 330